Some physiological aspects of gastric ulcer - Harjani Harjani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
The key of the development of gastric ulcer is that the unionised substances or the lipid soluble substances which can cross the lipoprotein part or the cell membrane cause a rapid back diffusion of H-ions from the lumina I part of the stomach to the mucosa] layer, and a rapid Na-ions secretion. It causes cell damage and histamin release. Histamin causes mucosal edema and increases gastric acid secretion. Strong and repeated insults of histamin release may develop mucosal erosions and then ulcers.It is suggested that the development of gastric ulcer is promoted among others by acid hypersecretion, mucous hypersecrerion, delayed mucosal cell turn-over, SIgA deficiency, rnucosal exposure to mucosa] damaging substances, and prolonged and repeated mucosa] ischemia.The pain of gastric ulcer is probably due mainly to the action of acid or other irritants on a sensitive region of the mucous membrane.Key Words : gastric mucosal barrier - I-12 receptor - cephalic phase of gastric secretion - emotional stress - cigarette smoker